2008
DOI: 10.1111/j.1551-2916.2008.02533.x
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Nanostructures for Multifunctional Single‐Walled Carbon Nanotube Reinforced Silicon Nitride Nanocomposites

Abstract: Colloidal processing was used to make highly dispersed aqueous composite suspensions containing single‐wall carbon nanotubes (SWNTs) and Si3N4 particles. The SWNTs and Si3N4 particles were stabilized into composite suspensions using a cationic surfactant at low pH values. Bulk nanocomposites containing 1.0, 2.0, and 6.0 vol% SWNTs were successfully fabricated using rapid prototyping. The survival of SWNTs was detected, using Raman spectroscopy, after high‐temperature sintering, up to 1800°C. The nanocomposites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 32 publications
2
43
1
Order By: Relevance
“…The slightly lower sintered densities of the MWCNT-containing ABS glass ceramics may be partly responsible for this lowering of hardness. Such reductions in hardness on the incorporation of CNTs in inorganic matrices have also been observed by others [11,15,28,29]. Fig.…”
Section: Hardness and Elastic Modulussupporting
confidence: 58%
“…The slightly lower sintered densities of the MWCNT-containing ABS glass ceramics may be partly responsible for this lowering of hardness. Such reductions in hardness on the incorporation of CNTs in inorganic matrices have also been observed by others [11,15,28,29]. Fig.…”
Section: Hardness and Elastic Modulussupporting
confidence: 58%
“…The evidence presented thus far ( Fig. 3C and D) [24,30] points to this hypothesis. With further crack propagation, eventually the SWNTs bridges far behind the crack tip will pullout or detach from the grain boundaries and/or fail.…”
Section: Toughening Mechanismsmentioning
confidence: 54%
“…This debate is further compounded by the fact that most researchers use the simple indentation test [2] to measure the toughness, which may not be a valid test in the case of these composites. [21,31,32] Independent, more difficult toughness tests (not based on indentation) show either no toughening, [21] significant toughening (two-fold increase over unreinforced ceramic), [24] or inconclusive results, [30] albeit in different composites. In light of the conflicting toughening results in ceramic/SWNTs composites, it is argued that the time has come to rethink the role of SWNTs in reinforcing ceramics.…”
Section: Toughening Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have studied the use of CNTs as reinforcements in alumina ceramic products that have been clinically applied in various fields as biomaterials. Reported improvements in the mechanical properties of CNT/alumina composites can be found in the literature [18,[29][30][31][32][33][34][35]. These studies showed only small improvement of strength, however, owing to the formation of microstructures that occurs when CNTs are dispersed homogeneously in the ceramic matrix.…”
Section: Discussionmentioning
confidence: 95%